If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + 2x) = 26 (2 * 3 + 2x * 3) = 26 (6 + 6x) = 26 Solving 6 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 26 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 26 + -6 6x = 26 + -6 Combine like terms: 26 + -6 = 20 6x = 20 Divide each side by '6'. x = 3.333333333 Simplifying x = 3.333333333
| 14x-6=10x+4 | | -6x+3+7x=4 | | -2lx+5l=8 | | 2x+4x(38-x)=136 | | bx+a=c | | 12x-6-8x=2x+2-6 | | -14+7m-19m=5m+20 | | 8=v+7 | | 3+6x+7x=-153 | | -2y-15=8y+15 | | 5x+4=10-5x-6 | | 2(2z-5)=3(z+5)+z | | -18+c=18+10c-13c | | -45=-2n+3 | | -20+4s-18=18-10s | | 4n=7n+2 | | 2x^2+10=8x | | 5x+2x=7x-6 | | C^2=9+16 | | -9+5x+6x=8 | | X+7-7x=-47 | | 2(10)-5y=8 | | -12+6n=15+4n+13 | | 8=-d+17 | | 7(4-3x)=2(8x-9) | | 7-14p= | | 17-6f=-5f-3 | | r+3.3=8 | | 8x-10=-8+3x | | -4=-8p+11+9p | | 6(-4x-1)=-150 | | -10-4x+8=10x-15 |